Antibiotics for the neurological complications of Lyme disease - Cadavid, Diego (Cochrane Database Syst Rev, 2016)
BACKGROUND: Various central nervous system‐penetrant antibiotics are bactericidal in vitro and in vivo against the causative agent of Lyme neuroborreliosis (LNB), Borrelia burgdorferi. These antibiotics are routinely used clinically to treat LNB, but their relative efficacy is not clear. OBJECTIVES: To assess the effects of antibiotics for the treatment of LNB. SEARCH METHODS: On 25 October 2016 we searched the Cochrane Neuromuscular Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, and Embase. We searched clinical trial registers on 26 October 2016. We reviewed the bibliographies of the randomized trials identified and contacted the authors and known experts in the field to identify additional published or unpublished data. There were no language restrictions when searching for studies. SELECTION CRITERIA: Randomized clinical trials of antibiotic treatment of LNB in adults and children that compared any antibiotic treatment, including combinations of treatments, versus any other treatment, placebo, or no treatment. We excluded studies of entities considered as post‐Lyme syndrome. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. MAIN RESULTS: We identified seven randomized studies involving 450 European participants with LNB for inclusion in this systematic review. We found no trials conducted in the United States. Marked heterogeneity among these studies prevented meta‐analysis. None of the studies included a placebo control on the initial antibiotic treatment, and only one was blinded. None were delayed‐start studies. All were active comparator studies, and most were not adequately powered for non‐inferiority comparison. The trials investigated four antibiotics: penicillin G and ceftriaxone in four studies, doxycycline in three studies, and cefotaxime in two studies. One study tested a three‐month course of oral amoxicillin versus placebo following initial treatment with intravenous ceftriaxone. One study was limited to children. The trials measured efficacy using heterogeneous physician‐ or patient‐reported outcomes, or both. In some cases cerebrospinal fluid analysis was included as an indirect biomarker of disease and outcome. None of the studies reported on our proposed primary outcome, 'Improvement in a measure of overall disability in the long term (three or more months).' None of the trials revealed any between‐group differences in symptom resolution in response to active treatment. In general, treatment was tolerated well. The quality of adverse event reporting, however, was low. AUTHORS' CONCLUSIONS: There is mostly low‐ to very low‐quality clinical evidence from a limited number of mostly small, heterogeneous trials with diverse outcome measures, comparing the relative efficacy of central nervous system‐penetrant antibiotics for the treatment of LNB. The few existing randomized studies have limited power and lack consistent and well‐defined entry criteria and efficacy endpoints. It is not possible to draw firm conclusions on the relative efficacy of accepted antibiotic drug regimens for the treatment of LNB. The majority of people are reported to have good outcomes, and symptoms resolve by 12 months regardless of the antibiotic used. A minority of participants did not improve sufficiently, and some were retreated. These randomized studies provide some evidence that doxycycline, penicillin G, ceftriaxone, and cefotaxime are efficacious in the treatment of European LNB. No evidence of additional efficacy was observed when, in one study, an initial antibiotic treatment with intravenous ceftriaxone was followed by additional longer treatment with oral amoxicillin. There is a lack of evidence identified through our high‐quality search strategy on the efficacy of antibiotics for treatment of LNB in the United States.